Toward a greater understanding of the market orientation and internal market orientation relationship. (18th August 2018) - Modi, Pratik; Sahi, Gurjeet Kaur
Abstract: The study explores the relationship between market orientation (MO) and internal market orientation (IMO) using the process model of MO development. Data from 370 nonprofit organizations were analyzed using structural equation modeling with maximum likelihood estimation technique. The comprehensive CFA marker method was used to partial out the influence of social desirability bias on the substantive relationships. The study finds that MO works through IMO to elicit desirable employee outcomes, which also contributes to performance outcomes. IMO does not offer direct performance benefits, but it partially mediates the effect of MO on employee-related outcomes. Competing models offering alternative explanations are ruled out empirically by the superior fit of the theoretical model with the data. The study integrates IMO in Kohli and Jaworski's model of antecedent and consequences of MO and encourages practitioners to embed IMO in their MO development plans.